Likuiditas dan Profitabilitas Perusahaan Manufaktur di ASEAN+3 - Lanemey Brigitha Pandeirot; Elvis Ronald Sumanti (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to examine the effect of liquidity on company profitability. The samples in this study were manufacturing companies in China, Indonesia, Malaysia, South Korea, Philippines, Singapore, Japan and Thailand. Liquidity in this study is proxied by using the current ratio. Profitability in this study is proxied by using net profit margin, return on assets, and return on equity. By using the fixed effect (FE) model in multiple regression, during the study period 2012-2016, there were 23,800 observations from 5,139 manufacturing companies in ASEAN+3 were found to have a positive effect on net profit margin, return on assets and return on equity. Furthermore, testing the differences in the effect of liquidity on profitability in each country shows mixed results.